(untitled) (KYAMC Journal, 2026)
Background: Metformin is recommended as the first-line drug for people with Type 2 Diabetes Mellitus (T2DM) who cannot achieve glycemic control by lifestyle changes. However, there are no clear recommendations for the optimal agent to combine with metformin. Empagliflozin is an effective and selective sodium-glucose co-transporter 2 (SGLT2) inhibitor that reduces blood sugar levels and can be used as monotherapy or as an add-on to existing therapy. Materials and Methods: The Department of Pharmacology and Therapeutics collaborated with Rajshahi Diabetic Association General Hospital to conduct a year-long quasi-experimental study on 60 uncontrolled T2DM patients (HbA1c > 7.0 to ≤ 10.5%) for over 12 weeks. Empagliflozin 10 mg (1 tablet) was administered as a third-line medication to each patient’s ongoing treatment and monitored at 6 and 12 weeks. Results: The mean systolic and diastolic blood pressures decreased from 129.7 mmHg to 118.3 mmHg (p < 0.001) and 81.7 mmHg to 78.9 mmHg (p = 0.03), respectively after 12 weeks of intervention. Only one (2%) patient had suffered from UTI. The mean serum creatinine after 12 weeks of intervention was 0.8 ± 0.1 mg/dl. The additional benefit (reduction of blood pressure) may be an added advantage as many diabetics may have concurrent hypertension. Conclusions: No significant incidences of UTI and hypoglycemia were seen in any patients, the drug could be considered safe. KYAMC Journal Vol. 16, No. 03, October 2025: 119-122.